Successful Treatment of Localized Pemphigus Foliaceus with Topical Pimecrolimus. (17th September 2013) - Tyros, G.; Kalapothakou, K.; Christofidou, E.; Kanelleas, A.; Stavropoulos, P. G.
Abstract : We report the case of successful treatment of a 79-year-old male patient with recurrent pemphigus foliaceus with pimecrolimus cream 1% once daily for 40 days. The patient initially presented with localized lesions on the scalp and nose area and was treated with systemic corticosteroids. At his fourth relapse within a period of 16 months, he refused any systemic treatment. Pimecrolimus cream was suggested to him as an alternative option.